POSSIBLE ASSESSMENT OF SALT TOLERANCE IN OCIMUM BASILICUM BY CHLOROPHYLL FLUORESCENCE - Rehana KHALIQ; Ovidiu TITA; Zafar Ullah ZAFAR (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The present study was carried out to evaluate the impact of NaCl on chlorophyll florescence in three ecotypes of sweet “basil” (Ocimum basilicum L.) i.e., Multan, Khanewal and Rajanpur. Four weeks old seedlings were treated by different concentrations of NaCl (0, 50, 100, 150, 200 mM). Results showed that the increasing salinity stress had a negative impact on QY (Quantum yield), NPQ (Non photochemical quenching) and OJIP in three ecotypes of Ocimum basilicum L. From the findings, it is obvious that salt stress had a slight inhibitory effect in the first week of salt treatment. Under saline conditions as compared to non saline conditions dark adopted leaves of Rajan pur ecotype have reduced fv/fm ratio in third week of salt stress but decreased with increasing levels of salt stress in other two ecotypes. Therefore, analysis of the results showed that sweet basil might tolerate a level of salt stress up to 150 mM of NaCl and chlorophyll fluorescence can be used as a criterion for assessing salt tolerance in sweet basil as well as helpful to screen which ecotype might tolerate better the salinity stress. Our findings suggested that basil can be cultivated on salt effected soils up to moderate level that can be of potential importance in Ocimum basilicum production.